Abdominal tuberculosis: a clinical study in a tertiary care hospital - Krishnaswamy, Jawahar; Rahaman, Khalilur; S., Reshma; N., Bharath (International Surgery Journal, 2017)
Background: Abdominal tuberculosis is the sixth most common form of extrapulmonary site of infection after lymphatic, genitourinary, bone and joint, miliary and meningeal TB with a rising incidence in recent years. Tuberculosis can affect any part of the gastro-intestinal (GI) tract including anus, peritoneum and hepato-biliary system. The clinical manifestations of abdominal tuberculosis are non-specific and mimic various GI disorders and cause delay in diagnosis and management. The aim of this study is to study the incidence of abdominal tuberculosis, percentage of acute presentation, to study and analyse clinical presentation, various diagnostic modalities, role of surgery and to evaluate the spectrum of surgeries done for abdominal tuberculosis Methods: Study was done by analyzing 108 cases in our tertiary care hospital, Chennai, India, during the period of June 2015 to January 2016. All suspected and diagnosed cases of abdominal tuberculosis were included in the study. The relevant clinical information, laboratory results, microbiological and radiological investigations were recorded. Histopathological examination of all the resected or excised specimens was done to detect tuberculosis in all the cases. Results: Out of 108 cases with abdominal tuberculosis, the average age of presentation was between 21 and 40 years with a slight male predominance (male:female = 1.1:1). Abdominal pain (92%) was the most common presenting symptom followed by anorexia (70%), loss of weight (70%), and intestinal obstruction (13%). 29 cases underwent surgical management. All patients were put on anti-tubercular treatment and majority showed good response to therapy. Conclusions: Abdominal tuberculosis should be considered as a differential diagnosis in patients with vague GI symptoms. To diagnose abdominal tuberculosis, high degree of suspicion is needed, and its incidence being common in people with lower socioeconomic status. This study gives a basic outline of presentation, diagnosis and management of abdominal tuberculosis in developing country.